COVID-19 Pandemic: Risks and Uncertainties in Contemporary Society - Silva, Márcia Regina Farias da; Silva, Carlos Aldemir Farias da; Dutra, Maria da Conceição Farias da Silva Gurgel (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2021)
In contemporary society, the advancement of the new coronavirus (SAS-CoV-2) has made clear the relationships between society's actions and their consequences, both in the spread of the disease and, in the environmental issue, in the imbalance of ecosystems. In this sense, this study seeks to present a reflection on the relationship between modern science, the environment, and the health crisis of Covid-19, having as theoretical basis the studies of Ulrich Beck on risk society in the context of globalization. As a methodological procedure, a bibliography and documentary research were carried out. The study found that the current model of society can lead humanity to catastrophes at a global level, without the possibility of calculating the risk, since environmental problems are beyond the control of society and present many uncertainties, especially in the post-pandemic.